Winnipeg : a social history of urban growth, 1874-1914 - Artibise, Alan F. J. (McGill-Queen's University Press, 1975)
This study provides a reasonably detailed social history of Winnipeg: a description--or reconstruction--of the evolvement of an urban area. It endeavours to identify and describe the events, personages, trends, and movements which have played a key role in the development of Winnipeg.